Application of bipolar electrochemistry to accelerate dew point corrosion for screening of steel materials for power boilers. (1st April 2020) - Bankiewicz, Dorota; Vainio, Emil; Yrjas, Patrik; Hupa, Leena; Lisak, Grzegorz
Abstract: Maximized energy recovery in power boilers lowers the flue gas temperature. However, lowering the temperature too much may lead to problems with corrosion. The lowest operational temperature is often limited by the presence of sulphuric acid in the flue gas. Condensation of sulphuric acid may lead to severe corrosion of pre-heaters and flue gas duct parts. In this study, an experimental setup for accelerated dew point corrosion testing of steels using a concept of bipolar electrochemistry was developed. The bipolar electrochemistry was for the first time applied to study corrosion at conditions of condensing vapours of acid on the steel surface. The method allows simultaneous testing of several samples at both oxidizing and reducing conditions. In the present work, several commercial boiler steels were tested for their resistance to the dew point corrosion. It was found that bipolar electrochemistry can easily be used to accelerate corrosion for fast screening of different steel materials in simulated, dew point corrosion conditions as present in the boiler's cold-end. The electron microscopy (SEM/EDX) analyses showed that corrosion was accelerated on carbon and high alloy steels with the use of bipolar electrochemistry. Generally, stainless steels showed very good corrosion resistance and no adverse effects caused by hot H2 SO4 vapours were observed.